An evaluation of the feasibility of using Moodle to develop an online learning program for the Grade 12 Literature component of the First Additional Language syllabus in South Africa - Van Rooyen, Marinda (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Modern Foreign Languages))--University of Stellenbosch, 2011.